2015
DOI: 10.1177/1748895815590201
|View full text |Cite
|
Sign up to set email alerts
|

Voices of the incarcerated father: Struggling to live up to fatherhood

Abstract: Despite overwhelming evidence that imprisonment has negative consequences for family members, very few studies have explored the mechanisms by which incarceration affects families and children. In particular, the father role is crucial to family members. Together with the fact that there have been few studies on incarcerated fathers and their relationships with significant others, this study draws on the theoretical bases and predictions of the identity theory to explore qualitatively the extent of expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 42 publications
(42 reference statements)
2
25
0
2
Order By: Relevance
“…Childhood trauma is considered as the combination of different factors among which the history of their family members" incarceration is very vital (Chui, 2016;Altintas and Bilici, 2018;Caravaca-Sánchez et al, 2019). Therefore, the incarcerated females are more likely to face more delinquent outcomes from their children or other family members.…”
Section: The Link Between Parental Incarceration and Childhood Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood trauma is considered as the combination of different factors among which the history of their family members" incarceration is very vital (Chui, 2016;Altintas and Bilici, 2018;Caravaca-Sánchez et al, 2019). Therefore, the incarcerated females are more likely to face more delinquent outcomes from their children or other family members.…”
Section: The Link Between Parental Incarceration and Childhood Traumamentioning
confidence: 99%
“…But they witnessed that mothers with children always enjoy better facilities which are applicable to their children. However, parents" incarceration in many cases are liable for childhood trauma which can lead them to a crime-prone lifestyle in their later life (Chui, 2016;Altintas and Bilici, 2018;Caravaca-Sánchez et al, 2019).…”
Section: 38 Difficulties To Meet With Childrenmentioning
confidence: 99%
“…Por meio de entrevistas realizadas com exdetentos em Hong Kong, a pesquisa conduzida por Chui (2016) (2005) que, por sua vez, buscou compreender as percepções de pais encarcerados sobre a paternidade e a natureza de envolvimento mantido com seus filhos durante o período de prisão, pontuou que a prisão representava um período de "dormência" dos pais no que se refere à paternidade. Ademais, a liberdade era entendida como uma oportunidade de começar de novo, de estar perto e fazer a diferença na vida dos filhos.…”
Section: Métodounclassified
“…Os nove artigos que não eram sustentados por uma abordagem de gênero eram, em sua maioria, provenientes dos EUA (Arditti et al, 2005;Geller et al, 2012;Geller et al, 2011;Perry & Bright, 2012;Secret, 2012;Schwartz-Soicher et al, 2011;Swisher & Waller, 2008); exceto por um de Hong Kong (Chui, 2016) e um da África do Sul (Prinsloo, 2007). As pesquisas americanas trouxeram questões relativas ao bem-estar dos filhos de pais encarcerados, porém com uma ótica ainda tradicional dos papéis de pai na família.…”
Section: Métodounclassified
“…Empirical studies have repeatedly shown that several factors other than past criminal behaviour influence an individual's ability to desist or not from such behaviour in the future. These include, addiction and substance abuse issues; lack of paid employment; poor access to training and education; a lack of family support; types of friends; and age (Markson et al 2015, Chui 2016. Furthermore, the poorest members of society, alongside those who belong to racial and ethnic minority groups, are disproportionately represented within western criminal justice systems, and the underpinning self-justifying logic of the criminal record database perpetuates, for many of these individuals, their lived biography of social marginalisation and exclusion: it confirms that they will always belong at the edges of society (Pager 2008, Henley 2014, Fox 2016.…”
Section: Criminal Histories Desistance and Employmentmentioning
confidence: 99%